Petrology and Geochemistry of Igneous Rocks in Gunung Badak Complex, Ciletuh Palabuhanratu Geopark, Sukabumi, West Java - Rosana, Mega Fatimah; Endyana, Cipta; Sentosa*, Millati Amalia (Aceh International Journal of Science and Technology, 2025)
Gunung Badak Complex is located in Ciletuh Palabuhanratu UNESCO Global Geopark, which preserves significant records of tectonic evolution in Southern West Java. This research aims to characterize igneous rocks and interpret tectonic implications. The methodology includes petrographic analysis, major element geochemical characterization using X-Ray Fluorescence (XRF), and trace elements and Rare Earth Element (REE) analysis using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) from 8 selected samples. The results identify three distinct rock groups consisting of diorite (SiO 51.5-52.48%), basalt (SiO 50.69-52.52%), and serpentinized peridotite (SiO 40.59%, MgO 34.63%). Diorite and basalt exhibit tholeiitic affinity with low KO (0.25-0.69%), Mg# 49.67-58.13, indicating early-stage island arc magmatism. Serpentinized peridotite exhibits residual harzburgite characteristics with Mg# 89.29. Trace element geochemistry shows enrichment of LILE (Cs, Ba, Pb, Sr) relative to HFSE (Nb, Zr), with negative Nb-Ta anomalies and La/Nb ratios of 2.21-3.75 typical of subduction environments. Diorite-basalt displays moderate LREE enrichment ((La/Yb)N 1.40-2.63), while serpentinized peridotite shows LREE depletion ((La/Yb)N 0.54). Dy/Yb ratios (1.20-1.91) indicate magma sources from partial melting of spinel peridotite at depths 50 km. The geodynamic model indicates that serpentinized peridotite originated from lithospheric mantle in a supra-subduction zone (SSZ) environment during Eocene subduction initiation, while diorite and basalt formed during early Miocene island arc magmatism (~22 Ma).